2017
DOI: 10.1136/injuryprev-2017-042467
|View full text |Cite
|
Sign up to set email alerts
|

Injury upon injury: a prospective cohort study examining subsequent injury claims in the 24 months following a substantial injury

Abstract: More than half of those with an ACC entitlement claim injury incurred further injury events that resulted in a claim in the following 24 months. Greater understanding of these subsequent injury events provides an avenue for injury prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(18 reference statements)
1
9
0
1
Order By: Relevance
“…Trouble accessing healthcare services for one’s injury predicted problems with usual activities and with anxiety/depression. This has important implications given the adverse impact that psychological morbidity has been found to have on injury recovery [ 40 ] and outcomes [ 41 , 42 ]. Our study found that having a depressive-type episode in the year prior to injury increased the risk of having a summed EQ-5D score of ≥ 7 at 12-months post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…Trouble accessing healthcare services for one’s injury predicted problems with usual activities and with anxiety/depression. This has important implications given the adverse impact that psychological morbidity has been found to have on injury recovery [ 40 ] and outcomes [ 41 , 42 ]. Our study found that having a depressive-type episode in the year prior to injury increased the risk of having a summed EQ-5D score of ≥ 7 at 12-months post-injury.…”
Section: Discussionmentioning
confidence: 99%
“…For participants we are unable to track using these available contact details, we will: (i) trace using the electoral roll or (ii) trace via updated contact details held by ACC (following ethical approval), as done in the earlier POIS project. We know from our research that 58% of POIS participants went on to experience a new injury event reported to ACC in the 24 months following their SIE [40]. Therefore, with ACC as an active collaborator, we expect to obtain reliable updated contact details for most harder-to-track POIS-10 participants.…”
Section: Pois-10 Recruitmentmentioning
confidence: 99%
“…POIS participants were interviewed 3, 12, and 24 months post-injury, providing information about their pre-injury characteristics (at the 3-month interview) and their injury experiences and outcomes at each follow-up time point [38]. Self-reported interview data were linked with information from large administrative datasets, including claims e-data from ACC (e.g., earnings-related wage compensation, health professional utilisation, treatment costs, and additional injury events) and injury-related hospitalisations recorded in the Ministry of Health (MoH) national minimum data set (NMDS) [39,40]. Results for the whole cohort, and specifically for Māori [6,[34][35][36][37], revealed key predictors of disability [30,31,41], participation in paid work [36,[42][43][44][45] and unpaid activities [46], other health outcomes including subsequent injury events [40,47], HRQL [46], physical functioning [7], and wellbeing outcomes [33,48] using validated measures.…”
Section: Contribution Of Poismentioning
confidence: 99%
See 1 more Smart Citation
“…18 In addition to being more common, occupational injuries are more severe and more costly among workers with hearing and visual impairments [32][33][34] and other persistent disabilities. [35][36][37][38] In research using data from the National Longitudinal Survey of Youth, having an early-onset (before age 23) health-limiting condition was one of the strongest predictors of recurrent occupational injury. 39 Second, in a Washington State WC-based study, more than half of workers surveyed thought their permanent impairment put them at higher risk of being reinjured at work.…”
Section: Introductionmentioning
confidence: 99%